2016
DOI: 10.1002/jlcr.3368
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and evaluation of 186Re‐idarubicin: a novel agent for diagnosis and treatment of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma is a widely prevalent cancer, and hence, the development of radiopharmaceuticals for its management is an important issue. In the current investigation, the complexation of idarubicin with (186) Re was studied. Optimum labelling conditions were found to be 4 mg idarubicin, 1.5 mg stannous chloride dihydrate and ~70 MBq Re-186 at pH 7. The complex showed ~97.6% RCY value at 20 min and remained stable up to 24 h in the presence of 2.5 mg ascorbic acid. Molecular docking was performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The maximum T/NT ratio was 3.73 ± 0.2 at 4 hours post injection. This ratio was higher than recently developed agents such as 99m TcN‐MAG‐AMCPP (1.83 after 1 hour), 99m Tc‐DMSAme (2.49 at 2 hours), and 186 Re‐idarubicin(2.93 at 2 hours) . Also, it showed a comparable result to 99m Tc‐sunitinib (3.2 after 3 hours), 99m Tc(CO)3‐labeled chlorambucil analogue (3.2 after 3 hours) .…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The maximum T/NT ratio was 3.73 ± 0.2 at 4 hours post injection. This ratio was higher than recently developed agents such as 99m TcN‐MAG‐AMCPP (1.83 after 1 hour), 99m Tc‐DMSAme (2.49 at 2 hours), and 186 Re‐idarubicin(2.93 at 2 hours) . Also, it showed a comparable result to 99m Tc‐sunitinib (3.2 after 3 hours), 99m Tc(CO)3‐labeled chlorambucil analogue (3.2 after 3 hours) .…”
Section: Resultsmentioning
confidence: 67%
“…This ratio was higher than recently developed agents such as 99m TcN-MAG-AMCPP (1.83 after 1 hour), 23 99m Tc-DMSAme (2.49 at 2 hours), 24 and 186 Re-idarubicin(2.93 at 2 hours). 25 Also, it showed a comparable result to 99m Tc-sunitinib (3.2 after 3 hours), 26 99m Tc(CO)3-labeled chlorambucil analogue (3.2 after 3 hours). 27 In comparison with 99m Tc-paclitaxil, compound 2 reached the maximum T/NT ratio (3.73) only 4 hours post injection, while 99m Tc-pacilataxil reached the its maximum ratio 24 hours (6.83) post injection.…”
Section: Biodistribution Study Of Compoundmentioning
confidence: 65%
“…The amount of stannous chloride less or greater than 0.5mg, such as 0.01 or 3mg leads to the RCY of 186 Re-cefixime decreasing to 75.6±1.5 or 60±1.2%, respectively. The RCY of 186 Re-Cefixime decreased in the low amount of SnCl 2 that may be attributed to its insufficient concentration to reduce the rhenium (VII) (ReO 4 -) to lower oxidation states (El-Kawy & Talaat, 2016). While most of the ligand molecule was consumed in the formation of complex, the perhenate is reduced to insoluble rhenium (IV) ReO 2 .xH 2 O in the absence of ligand at the high concentration of stannous chloride (Azmi et al, 2013).…”
Section: Effect Of Stannous Chloride Dihydrate Amountmentioning
confidence: 99%
“…Idarubicin, a derivative of daunorubicin and an antileukemic medication, is used for the therapy of breast and lymphomas cancers (El‐Kawy & Talaat, ). The findings of an investigation indicated that GSPE reduced growth inhibitory effects of idarubicin on Chang liver cells, as well as the number of apoptotic cells.…”
Section: Chemical‐induced Toxicitymentioning
confidence: 99%